The complete mitochondrial genome of Cerithidea sinensis (Philippi, 1848) - Xu, Youhou (Mitochondrial DNA B Resour, 2019)
Cerithidea sinensis is a common and important component of mangrove ecosystem. In this study, the mitochondrial genome of C. sinensis was determined for the first time using next-generation sequencing; the overall base components of mitogenome consisting of 15633 bp was 31.14% for A, 35.70% for T, 16.65% for G, 16.51% for C, and its GC content was 33.16%. The mitochondrial circular genome was composed of 13 protein-coding genes, 22 tranfer RNAs, and 2 ribosomal RNAs. Polygenetic analysis showed that the C. sinensis was more closed to Semisulcospira libertina than Turritella bacillum and Tylomelania sarasinorum. We may speculate that the C. sinensis is evolved from freshwater species.